Different sound exposures causes alterations in stress-related serum indicators, behaviors, and cecal microbiota of green-shell egg-laying chickens under different stocking densities - Shiwen Cao; Manhong Ye; Wanhong Wei; Fengping Yang (PeerJ)
Sound and stocking density are two common factors which influence the performance and welfare of layers. Accumulated studies have been conducted on the impacts of the two factors on production performance, while knowledge regarding the impacts of the two factors and their interactions on stress-related serum indicators, behaviors, and cecal bacterial communities in laying hens is still limited. A 3 × 3 factorial design with three sound sources (natural sound (NS), instrumental music (IMS), or mixed road noise (MRS)) and three stocking densities (low density (LD), medium density (MD), and high density (HD)) was used in this 24-day experiment, in which 378 30-week-old Xiandao green-shell layers were randomly distributed into nine treatments with six replicates per treatment. At the 3rd, 12th, and 24th experimental day, we evaluated the serum levels of adrenocorticotropic hormone (ACTH) and corticosterone (CORT) and recorded stress-related animal behaviors. At the end of the experiment, 16S rRNA gene amplicon sequencing of the cecal bacterial communities was performed. Our results confirmed that MRS and HD induced significantly elevated serum ACTH and CORT levels, and were correlated with significantly increased feather pecking behavior. IMS and LD were associated with enhanced preening behavior and reduced feather pecking behavior. LD significantly increased the Firmicutes/Bacteriodetes ratio and IMS significantly enriched the beneficial Lactobacillus population. Based on the obtained results we proposed that music exposure and reduced stocking density were helpful in reducing stress and improving cecal bacterial profile, which were beneficial for improving layers’ health status and welfare.